The Transformation of Deep Learning in the Merdeka Curriculum at Madrasahs: Instructional Leadership and Strengthening the 6C Competencies - Muhammad Fariz Ashari; Nur Khoiri (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study was motivated by the demands of 21st-century educational transformation, which promotes more meaningful, reflective, and learner-centered learning through the implementation of deep learning in the Merdeka Curriculum at madrasahs. The study aims to analyze the transformation of deep learning, the role of the madrasah principal’s instructional leadership, and its contribution to strengthening students’ 6C competencies at MA Sultan Fatah Demak. The research employs a qualitative approach using a case study design. Data were collected through semi-structured interviews, non-participant observation, and documentation involving the madrasah principal, the vice principal for curriculum, and teachers. Data analysis was conducted using the Miles, Huberman, and Saldaña model through data condensation, data presentation, and drawing conclusions. The results of the study indicate that the implementation of deep learning drives a shift in learning from teacher-centered to student-centered learning that is more active, collaborative, based on higher-order thinking skills (HOTS), and reflective. The instructional leadership of the madrasah principal plays a crucial role in fostering an academic culture, supervising learning, and facilitating professional collaboration among teachers. Furthermore, the implementation of deep learning contributes to the holistic strengthening of students’ 6C competencies. This study concludes that the deep learning transformation in madrasahs is not merely a change in teaching methods but also a shift in learning culture that supports sustainable 21st-century learning.